SALAT'S IMPACT ON MENTAL RESILIENCE AND SUSTAINED PSYCHOICAL WELL-BEING - Amiruddin, Muhammad; Waez, Abdurrahman; Salafi, Muchamad Asafin; Maghfira, Bhebyalna; Effendy, Maulina Rosalia; Praja, Shafa Ananti (International Journal of Multidisciplinary Reseach, 2025)
It studies reviews the relationship between practice of ṣalāh (prayer) and mental health from the perspectives of modern psychology and Islamic values. A descriptive-narrative literature review was conducted, analysing peer-reviewed studies and relevant scholarly reports published between 2020-2025. Findings indicate that regular, mindful prayer contributes to reductions in stress and anxiety, enhances inner calm, & strengthens psychological well-being through mechanisms such as emotion regulation, meaning-making, routine coping, & spiritual connectedness. Prayer also functions as a culturally consonant, non-pharmacological coping strategy within Muslim communities. However, the evidence is heterogeneous, and integration of religious elements into mental health practice requires culturally sensitive, evidence-based, and ethically guided approaches. Overall, consistent & reflective practice of ṣalāh can be considered a valuable component in promotive & preventive mental health efforts.